Pelatihan pembuatan dan editing video bagi guru SD untuk menghadapi Era Industri 4.0 - Yosi Nur Kholisho; Baiq Desi Dwi Arianti; Jamaluddin Jamaluddin; Rasyid Hardi Wirasasmita; Kholida Ismatulloh; Muhammad Zamroni Uska; Ahmad Fathoni (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
The Industrial 4.0 Era encourages educators to be able to apply information technology in the learning process. One application of technology in the learning process is the use of learning videos. Especially during the current Covid 19 pandemic that applies online learning, videos can be an alternative source for learning. However, in reality, many teachers in Indonesia cannot make learning videos. Online learning is currently mostly only in the form of providing material from textbooks, discussions via WA, visiting students' homes to give assignments, and so on, so it is not optimal. Therefore, this training activity aims to train teachers in making learning videos so that teachers have other alternatives as a source of student learning. This activity is in the form of training in making and editing videos using the Bandicam application, Microsoft PowerPoint 2013, and the Kinemaster application. The results of this activity are participants/teachers for the Bandicam application with a 100% success rate, Microsoft PowerPoint 2013 100% success rate, Kinemaster the first stage success rate 70%, then the second stage 100%.